Impact of WTO Agreement on Capital Structure of Pharmaceutical Industry in India - Shanmugasundaram, G.; Gounasegaran, C. (Indian Journal of Finance, 2009)
When the International norms recognized the product patent, the Government of India enacted the Indian Patent Act in 1970(process patent) with the objectives of allowing the domestic companies to grow. Today Indian pharma has been ranked number three in terms of volume and thirteen in terms of value. The survival of the pharmaceutical companies after signing the TRIPS is dependent on Research and Development (R&D). Both Indian companies and MNCs are gearing themselves, towards contributing to investments in the R&D since 1995 after the Government of India signed the WTO. Hence an attempt has been made to assess whether there are any changes in the capital structure of the pharmaceutical industry between the two periods in view of the TRIPS agreement. The ratio analysis, paired t-test, chow test shows there is a significant shift from debt funds to share holders fund from period-1 to period-2 in the case of Indian pharmaceutical industry. But if we look at the MNCs, there is no change in the ratios or a significant change in the t value and the chow test for MNCs to test the structural shift has shown no significant change in the capital structure between the two periods. This is because the MNCs were in the product patent even before the WTO TRIPs agreement December, 1994 and hence there was no need of change in the capital structure.